Africa, amazing Africa country by country - Atinuke ; illustrated by Mouni Feddag (London Walker Books, 2020)
Atinuke?s first non-fiction title is a major publishing event: a celebration of all 55 countries on the African continent! Her beautifully-written text captures Africa?s unique mix of the modern and the traditional, as she explores its geography, its peoples, its animals, its history, its resources and its cultural diversity. The book divides Africa into five sections: South, East, West, Central and North, each with its own introduction. This is followed by a page per country, containing a delightful mix of friendly, informative text and colourful illustrations. The richest king, the tallest sand dunes and the biggest waterfall on the planet are all here, alongside drummers, cocoa growers, inventors, balancing stones, salt lakes, high-tech cities and nomads who use GPS! This is non-fiction at its most exciting, exhilarating and energetic, illustrated with passion and commitment by a great new talent, Mouni Feddag.
Includes index
Keywords: Africa